Retrospective analysis of perineal herniorrhaphy with cone-shaped polypropylene mesh in dogs: technique description and outcome - Heishima, Tatsuya; Ishigaki, Kumiko; Seki, Mamiko; Teshima, Kenji; Yoshida, Orie; Iida, Kaito; Takeuchi, Ryo; Asano, Kazushi (Frontiers in Veterinary Science, 2023)
Introduction: This study aimed to describe the technique for the surgical repair of perineal hernia (PH) in dogs using a polypropylene mesh (PM) and to evaluate its outcomes. Methods: All dogs were placed in the Trendelenburg position. Castration and caudal celiotomy for cystopexy and colopexy were performed as needed. Ipsilateral perianal incision was performed in the affected hernia side. A PM was formed a cone-shape with suturing and placed in hernial foramen. The PH was repaired with suturing between PH and pelvic diaphragm including the sacrotuberous ligament, internal obturator muscle, and external anal sphincter muscle. The medical records of all dogs were reviewed to evaluate signalment, perioperative findings, postoperative complications, and prognosis. Results: Of the 22 dogs, 15 were intact, and 7 were previously neutered. The median age and body weight were 10 years and 6.8 kg, respectively. The PH reconstruction using a cone-shaped PM was feasible in all dogs. The median operative time was 60.5 min for unilateral PH and 109 min for bilateral PH. Major postoperative complications occurred in seven dogs (32%), and three dogs (14%) had a recurrence of PH. In the long-term (> 2 weeks) follow-up period, 16 dogs (73%) had an excellent prognosis. Discussion: Our study suggests that PH reconstruction surgery using a cone-shaped PM may be a viable treatment method for PH in dogs. Therefore, a cone-shaped PM could serve as an alternative treatment option for canine PH reconstruction.